Effect of degeneration stage on non-viral tissue transfection of rd10 retina ex vivo - Jiao Zhang; Ziyu Bing; Corinne Marie; Zsuzsanna Izsvák; Frank Müller; Gabriele Thumann; Peter Walter; Sandra Johnen (Molecular Therapy: Nucleic Acids)
Gene therapy has great potential for the treatment of inherited retinal diseases, as evidenced by the progress and ongoing research. Using the Sleeping Beauty (SB) transposon system, we developed a non-viral gene delivery system for electroporation-based transfection of rd10 retinas ex vivo. SB100X transposase and Venus transposon plasmids were transfected at a ratio of 1:16 into rd10 retinas of different ages and corresponding wild-type (WT) controls. Transfection efficiency was assessed by fluorescence microscopy and transfected cells were identified by immunohistochemistry. Retinal integrity and cell viability were assessed by FITC-dextran electroporation, histology, and apoptosis assay. The highest transfection efficiency was observed in degenerated stages P61 and older, with Müller cells being the only transfected cell type. A 31% reduction in transposon plasmid size resulted in a 1.5-fold increase in transfection efficiency. Integrity and morphology of degenerated retinas were preserved after electroporation-based plasmid transfer; the number of apoptotic cells in the inner nuclear layer (INL) was reduced by half compared to WT controls. We demonstrated that electroporation-based delivery of the SB transposon system resulted in efficient transfection of degenerated retinas. Our results are an important first step toward the combined use of retinal prostheses and gene therapy to improve the treatment of inherited retinal dystrophies.